Professional development in language testing and assessment: a case study of supporting change in assessment practice in in-eervice EFL teachers in Thailand - Chinda, Bordin (2009)
This longitudinal qualitative study concerns the investigation of the impact of a professional development (PD) programme conducted at an English department in Thailand. The PD programme was carried out as a series of nine in-service workshops with five non-native English as a Foreign Language (EFL) teachers in the English Department. The workshops aimed to provide these teachers with theoretical and practical understanding of performance-based language assessment with a focus on the rating process. In the investigation of the impact of the PD on these teachers, individual and focus group interviews were used as the research methods. From the analysis of the data, guided by Grounded Theory, the findings show that the PD programme had a positive impact on the teachers who participated in the workshops. These teachers have become aware of their rating styles, established their own consistent rating styles, become confident when rating students’ performances, become critical to the assessment practices, realised roles of teachers in assessment, and recognised possibilities of changes in assessment. In other words, they have become more self-consistent when rating their students’ performances and they have become more critical to the assessment being used in the department. The insights gained from this research pose the implications for professional development, indigenous rating criteria and collaborative action research.